Capacidades dinámicas frente a la incertidumbre: una mirada desde la gestión universitaria (2019)
The study is part of a research conducted at the Dr. Rafael Belloso Chacín Private University, located in Maracaibo, Venezuela; with the purpose of analyzing the dynamic capacities of the university organization in the face of uncertainty, with the design, techniques and tools of qualitative research, from the post-positivist paradigm and experiential introspective approach, through the dialogic interpretation made to the emerging units arising from six in-depth interviews involving eight subjects participating in the private university. It was possible to discern by way of conclusion that when the private university is alert and prepared to act effectively, it “shields” itself from uncertainty as its environment; that even when the rhythm of its sustained growth has been affected, its dynamic capabilities in continuous feedback, have been the basis of staying at the forefront in the supply and demand of the service it provides, in the transfer of knowledge, its active participation and fundamental role that he plays as a social actor in Venezuelan society, beyond the country’s borders.